COVID-19 and its impact on student-athlete depression and anxiety: the return to campus - Economou, P. J.; Glascock, V.; Louie, M.; Poliakova, P.; Zuckerberg, W. (The Sport Journal, 2021)
The COVID-19 pandemic prompted the NCAA to abruptly cancel all sporting events, to help slow the spread of the virus. As such, measures such as social-distancing and work from home orders, were implemented nationwide. While effective, both safety measures are socially disruptive with the potential to cause psychological disturbances such as post-traumatic stress disorder (PTSD), depression, anxiety, and other behavioral disorders. To date, there is no literature that examines the consequences of abrupt mid-season cancellation for student-athletes, and the subsequent return to campus in Fall of 2020 brought on by a global crisis like the COVID-19 pandemic. To explore the mental health consequences of such termination and subsequent return to campus, student-athletes were surveyed on their experience with returning to campus amidst a global pandemic. Our results indicate that there were increased feelings of depression and anxiety upon returning to campus in Fall 2020.